Association of a pro-inflammatory diet with type 2 diabetes and hypertension: results from the Ravansar non-communicable diseases cohort study - Samira Arbabi Jam; Shahab Rezaeian; Farid Najafi; Behrooz Hamzeh; Ebrahim Shakiba; Mehdi Moradinazar; Mitra Darbandi; Fatemeh Hichi; Sareh Eghtesad; Yahya Pasdar (BMC, 2022)
Abstract Background Most non-communicable diseases (NCDs) are associated to diet and inflammation. The Dietary Inflammatory Index (DII) is a developed and validated self-assessment tool. The study was conducted to assess the association of DII with the hypertension (HTN) and type 2 diabetes mellitus (T2DM). Methods This cross-sectional analysis was conducted on 9811 participants aged 35 to 65 years from the Ravansar Non-Communicable Diseases (RaNCD) cohort study's baseline phase data. The DII was calculated using 31 food frequency questionnaire parameters (FFQ). Univariable and multiple logistic regression was used to derive the estimates. Results In healthy participants, the mean DII score was − 2.32 ± 1.60; in participants with T2DM, HTN, or T2DM&HTN, the mean DII score was − 2.23 ± 1.59, − 2.45 ± 1.60 and − 2.25 ± 1.60, respectively (P = 0.011). Males had a significantly higher pro-inflammatory diet than females (P <  0.001). BMI (body mass index), triglyceride, energy intake, smokers were significantly higher and socio-economic status (SES), physical activity and HDL-C were significantly lower in the most pro-inflammatory diet compared to the most anti-inflammatory diet. Participants with T2DM, HTN, and T2DM&HTN had significantly higher mean anthropometry indices (P <  0.001) and lipid profiles than healthy subjects (P <  0.001). After adjusting for age, gender, and physical activity, the probability of developing T2DM was 1.48 (95% CI: 1.19, 1.85) times greater in the fourth quartile of DII than in the first quartile. Conclusions The findings of this study showed that an anti-inflammatory diet are associated with HTN, T2DM, and the risk factors associated with these conditions. Modification of diet is recommended to reduce inflammation.